The Visual Acuity Outcome and Relevant Factors Affecting Visual Improvement in Pediatric Sporadic Chiasmatic–Hypothalamic Glioma Patients Who Received Surgery - Liao, Chihyi; Zhang, Heng; Liu, Zhiming; Han, Zhe; Li, Chunde; Gong, Jian; Liu, Wei; Ma, Zhenyu; Tian, Yongji (Frontiers in Neurology, 2020)
Background: The role and effectiveness of primary surgical treatment for sporadic chiasmatic-hypothalamic glioma (CHG) are not clear. The present study was to describe sporadic CHG visual acuity (VA) outcomes after surgery and to analyze the relevant factors affecting VA improvement. Methods: Forty-five pediatric sporadic CHG patients who met the inclusion criteria were included in a retrospective study. All patients received primary intratumor partial resection. Disease characteristics, treatment strategies, complications and VA outcome were analyzed. Univariate and multivariate analyses were performed to identify relevant factors of VA improvement. Receiver operating characteristic (ROC) analysis was performed to evaluate the predictive accuracy of measurement indexes. Results: There were 77 eyes of 45 children suffering from various levels of VA impairment before surgical treatment, and only 13 eyes had normal vision. Patients with resection extents >70%, 50-70%, and <50% accounted for 26.67%, 24.44%, and 48.89%, respectively. The percentages of VA maintained and deteriorated in normal vision eyes were 61.54% and 38.46%. The percentages of VA improved, maintained, and deteriorated in visually impaired eyes after surgery were 29.87%, 45.45%, and 24.68%, respectively. There was a positive correlation between the IVA level and VA improvement. There was no significant difference in VA improvement between the different resection extents. Blindness occurred in approximately 4.4%. Approximately 11.1% of the children had complications that affected quality of life, which correlated with resection extent. IVA and tumor size were correlated with VA improvement. The AUC for IVA+tumor size predicting VA improvement was 0.831. The cut-off points for IVA level and tumor volume were 4.5 and 43.50 cm3, respectively. Conclusions: IVA and tumor size were correlated with VA improvement after primary intratumor partial resection. Children with IVA ≥ level 5 were more likely to achieve visual improvement after decompression surgery, but decompression had limited effectiveness on vision improvement in patients with tumor volumes ≥ 43.50 cm3. Performing resections less than 50% was safe and did not reduce the effect of decompression to improve VA.